2019
DOI: 10.1055/s-0038-1675245
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes in Volar-Displaced Distal Radius Fractures Patients with Marginal Rim Fragment Treated by Volar Distal Locking Plates

Abstract: Background Treatment of volar-displaced distal radius fractures (DRF) accompanied by marginal rim fragment has recently been actively discussed. It is difficult to obtain a sufficient buttress effect on this fragment. Therefore, we actively apply a distal volar locking plate (DVLP) to fractures with this fragment. Here, we report the treatment outcomes and caveats of surgery of fractures with this fragment. Materials and Methods The subjects were 32 patients (male: 11, female: 21, and mean age: 59.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In 2004, Harness et al reported that treatment of DRF with VLFF using an existing volar locking plate is difficult due to its anatomical characteristics [ 20 ]. However, new DVLP applicable to volar-displaced fractures distal to the watershed line have recently been developed, and treatment of volar-displaced DRF with VLFF using DVLP has improved [ 15 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2004, Harness et al reported that treatment of DRF with VLFF using an existing volar locking plate is difficult due to its anatomical characteristics [ 20 ]. However, new DVLP applicable to volar-displaced fractures distal to the watershed line have recently been developed, and treatment of volar-displaced DRF with VLFF using DVLP has improved [ 15 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many cases that were difficult to treat due to postoperative re-displacement were of volar-displaced DRF with VLFF, and re-displacement on the volar side developed after surgery because PVLP was selected for these volar-displaced fractures or DVLP was selected, but the plate placement site was inappropriate [12][13][14]. Based on these reports, we cover VLFF and sufficiently apply buttress fixation as a treatment strategy using DVLP, considering that volar-displaced DRF with VLFF has a high risk for postoperative displacement [15] [15,21]. On the other hand, in dorsal-displaced fractures with VLFF, we consider secondary displacement to be caused by pulling by the short radiolunate ligament attached to VLFF through the dorsal displacement of carpal VLFF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone suture and hook plate stabilize the soft tissues (capsule, ligaments) in the case of a small bony fragment which includes the attachment of the short radiolunate and volar radioulnar ligaments. Fixation with distally positioned special volar plates can be a valid treatment option [14,15]. These special plates can provide a sufficient buttress effect on small distal fragments.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,10 Over the years, several implants and fixation strategies have been described with particular reference to distal radius volar rim fractures-these include hook plates, distal volar locking plates, wire loops, buttress pin clamps and headless screws. [9][10][11][12][13][14][15][16][17][18] However, these implants or fixation strategies have broadly been described for large, volar marginal fragments greater than 4e5 mm in size. There are only a few techniques addressing small, volar marginal fragments and such fractures continue to pose a challenge to orthopedic surgeons.…”
Section: Introductionmentioning
confidence: 99%